Distribution of a Sulfolane-Metabolizing Rhodoferax sp. Throughout a Contaminated Subarctic Aquifer and Two Groundwater Treatment Systems - Kasanke, Christopher P.; Willis, Michael D.; Leigh, Mary Beth (Frontiers in Microbiology, 2021)
An extensive plume of the emerging contaminant sulfolane has been found emanating from a refinery in Interior Alaska, raising questions about the microbial potential for natural attenuation and bioremediation in this subarctic aquifer. Previously, an aerobic sulfolane-assimilating Rhodoferax sp. was identified from the aquifer using stable isotope probing. Here, we assessed the distribution of known sulfolane-assimilating bacteria throughout the contaminated subarctic aquifer using 16S-rRNA-amplicon analyses of ~100 samples collected from groundwater monitoring wells and two groundwater treatment systems. One treatment system was an in-situ air sparging system where air was injected directly into the aquifer. The other was an ex-situ granular activated carbon (GAC) filtration system for treatment of private well water. We found that the sulfolane-assimilating Rhodoferax sp. was present throughout the aquifer but was significantly more abundant in groundwater associated with the air sparge system. The reduction of sulfolane concentrations combined with the apparent enrichment of sulfolane degraders in the air sparging zone suggests that the addition of oxygen facilitated sulfolane biodegradation. To investigate other environmental controls on Rhodoferax populations, we also examined correlations between groundwater geochemical parameters and the relative abundance of the Rhodoferax sp. and found only manganese to be significantly positively correlated. The sulfolane-assimilating Rhodoferax sp. was not a major component of the GAC filtration system, suggesting that biodegradation is not an important contributor to sulfolane removal in these systems. We conclude that air sparging is a promising approach for enhancing the abundance and activity of aerobic sulfolane-degraders like Rhodoferax to locally stimulate sulfolane biodegradation in situ.